2012
DOI: 10.1364/boe.3.002636
|View full text |Cite
|
Sign up to set email alerts
|

In situ structural and microangiographic assessment of human skin lesions with high-speed OCT

Abstract: We demonstrate noninvasive structural and microvascular contrast imaging of different human skin diseases in vivo using an intensity difference analysis of OCT tomograms. The high-speed swept source OCT system operates at 1310 nm with 220 kHz A-scan rate. It provides an extended focus by employing a Bessel beam. The studied lesions were two cases of dermatitis and two cases of basal cell carcinoma. The lesions show characteristic vascular patterns that are significantly different from healthy skin. In case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 27 publications
2
91
0
2
Order By: Relevance
“…Recent results of OCT angiography indicated that alterations of the vascular pattern are characteristic for different pathologic conditions, such as inflammation, or skin cancer. 147 The expectations to use functional OCT for enhanced diagnosis in dermatology are, therefore, high.…”
Section: Label-free Optical Angiographymentioning
confidence: 99%
“…Recent results of OCT angiography indicated that alterations of the vascular pattern are characteristic for different pathologic conditions, such as inflammation, or skin cancer. 147 The expectations to use functional OCT for enhanced diagnosis in dermatology are, therefore, high.…”
Section: Label-free Optical Angiographymentioning
confidence: 99%
“…Angiographic OCT based on flow characteristics provides additional vascular information within tissue, such as diameter, shape and distribution of blood vessels and their perfusion. Angiographic OCT has been applied to detecting abnormal vasculature of skin lesions such as port-wine stain (PWS) and basal cell carcinoma (BCC) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The functional extension of OCT angiography contrasts specifically blood flow against static tissue based on signal decorrelation without the need of contrast agents, thereby providing microvascular details with high contrast in strongly scattering tissue that are not visible with standard OCT [12]. OCT angiography has been applied to image facial or palmar human skin [13][14][15]. But even with focus field extension using Bessel beams or contrast enhancement algorithms to reduce the residual static artifacts, the effective angiographic imaging depth is well below 2 mm.…”
Section: Introductionmentioning
confidence: 99%